EXPLORING THE DETERMINANTS OF THE ACCEPTANCE OF WEARABLE FITNESS DEVICES IN MALAYSIA: A COMPARISON BETWEEN MALE AND FEMALE - Yap Way Zhe; Bryan Lam Jun Get; Sia Bee Chuan; Goh Hong Lip (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2022)
Wearable Fitness Devices (WFD) is a device that designed to assist their user to understand their fitness activity such as jogging, swimming, and cycling by providing feedback on the users’ fitness performance. Recently, it had become one of the fastest growing segment in the wearable devices industry globally, which attracted several giant technology companies to enter the market. Meanwhile in Malaysia, the rising awareness of physical activity among the Malaysian population and government had created a great market opportunity for the WFD provider to expand their businesses in Malaysia. In fact, the revenue generated from WFD market in Malaysia is expected to have a huge growth in recent years. However, in order for the WFD provider to compete with other competitor, it is important for them to understand the determinants of the WFD acceptance in Malaysia, especially knowing the differences between different market segment such as male and female to best design their devices and marketing strategy. Hence, this study approached to investigate the acceptance of WFD of male and female in Malaysia by applying an integrated Technology Acceptance Model (TAM). In order to achieve the research objective, this study employed a quantitative survey and distributed it through social media with a convenience sampling method and received 391 responses. Results shown that the perceived usefulness, perceived ease of use, perceived privacy and personal innovativeness have significant impact on the intention to use of WFD among male and female in Malaysia.